(untitled) (Universal International Scientific Journal, 2026)
This article discusses the pedagogical and psychological foundations of developing perceptual abilities of primary school students based on digital technologies. The use of information and communication technologies in modern education is an important factor in the development of students’ cognitive processes such as perception, observation, comparison and analysis. During the study, it was scientifically proven that classes organized using digital tools activate the sensory and cognitive activities of students. The results showed that digital technologies are an effective tool in developing perceptual abilities.